(untitled) (Scientific journal of the Fergana State University, 2023)
In this article the author reveals the problem of the origin and significance of Orientalism in Russian literature, the connection between East and West. Analyzing Pushkin’s "Imitations of the Koran", the author made linguistic conclusions concerning word formation, linguistics and loan-words.